Genome-Wide Identification of the ABC Gene Family and Its Expression in Response to the Wood Degradation of Poplar in Trametes gibbosa - Jia Zhao; Achuan Wang; Qian Wang (Journal of Fungi, 2024)
Wood-rotting fungi’s degradation of wood not only facilitates the eco-friendly treatment of organic materials, decreasing environmental pollution, but also supplies crucial components for producing biomass energy, thereby reducing dependence on fossil fuels. The ABC gene family, widely distributed in wood-rotting fungi, plays a crucial role in the metabolism of lignin, cellulose, and hemicellulose. Trametes gibbosa, as a representative species of wood-rotting fungi, exhibits robust capabilities in wood degradation. To investigate the function of the ABC gene family in wood degradation by T. gibbosa, we conducted a genome-wide analysis of T. gibbosa’s ABC gene family. We identified a total of 12 Tg-ABCs classified into four subfamilies (ABCA, ABCB, ABCC, and ABCG). These subfamilies likely play significant roles in wood degradation. Scaffold localization and collinearity analysis results show that Tg-ABCs are dispersed on scaffolds and there is no duplication of gene sequences in the Tg-ABCs in the genome sequence of T. gibbosa. Phylogenetic and collinearity analyses of T. gibbosa along with four other wood-rotting fungi show that T. gibbosa shares a closer phylogenetic relationship with its same-genus fungus (Trametes versicolor), followed by Ganoderma leucocontextum, Laetiporus sulphureus, and Phlebia centrifuga in descending order of phylogenetic proximity. In addition, we conducted quantitative analyses of Tg-ABCs from T. gibbosa cultivated in both woody and non-woody environments for 10, 15, 20, 25, 30, and 35 days using an RT-qPCR analysis. The results reveal a significant difference in the expression levels of Tg-ABCs between woody and non-woody environments, suggesting an active involvement of the ABC gene family in wood degradation. During the wood degradation period of T. gibbosa, spanning from 10 to 35 days, the relative expression levels of most Tg-ABCs exhibited a trend of increasing, decreasing, and then increasing again. Additionally, at 20 and 35 days of wood degradation by T. gibbosa, the relative expression levels of Tg-ABCs peak, suggesting that at these time points, Tg-ABCs exert the most significant impact on the degradation of poplar wood by T. gibbosa. This study systematically reveals the biological characteristics of the ABC gene family in T. gibbosa and their response to woody environments. It establishes the foundation for a more profound comprehension of the wood-degradation mechanism of the ABC gene family and provides strong support for the development of more efficient wood-degradation strategies.